Floristic-ecological comments on mexican iridaceans - Espejo-Serna, Adolfo; Lopez-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 1996)
The present status of the floristic-ecological knowledge of wild Mexican Iridaceae is defined. 16 genera and 98 species of Iridaceae, all of them belonging in the 4 tribes of the subfamily Iridoideae are registered from the country. The tribe Tigridieae has its principal center of radiation in Mexico, where 11 of 18 genera and 52 of approximately 130 species grow; of those, 3 genera (30 %) and 38 species (71.7 %) are endemic. One naturalized species is also known. The best represented genera of Iridaceae in Mexico are Sisyrinchium (40 spp.) and Tigridia (29 spp.). Endemism in the family at species level reaches 54.6 %. Data and comments on habitat, distribution and phytogeography of Mexican Iridaceae are included.